FINANCIAL FEASIBILITY ANALYSIS OF THE PONTIANAK STATE CATHOLIC RELIGIOUS COLLEGE (STAKATN) SANTA MARIA LECTURE BUILDING PROJECT - Lestari, Nina Septia; Lusiana, Lusiana; Rafie, Rafie (Fakultas Teknik Universitas Tanjungpura, 2024)
In the era of globalization and rapid advancement in higher education, Indonesian institutions face challenges in providing adequate facilities to support learning. The State Catholic College of Pontianak (STAKATN) Santa Maria aims to address this by constructing a new lecture building. This study conducts a financial feasibility analysis of the project using Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), Payback Period (PP), and Sensitivity Analysis. The analysis, based on a 25-year planning period, shows a positive NPV of IDR 12,949,362,911.15, an IRR of 9.36% (exceeding the discount rate of 5.1%), and a BCR of 1.231, indicating that the project's benefits exceed its costs. The Simple Payback Period is ten years, while the Discounted Payback Period is 14. Sensitivity analysis reveals that the project